Hodnocení finanční situace vybrané soukromoprávní korporace a návrhy na její zlepšení - Vaňková, Anna (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Tato bakalářská práce se zabývá hodnocením finanční situace vybraného podniku v letech 2012 až 2016. V první části práce je teoretickými poznatky přiblížena problematika finanční analýzy. Druhá část práce zahrnuje představení společnosti a praktickou aplikaci finančních ukazatelů. V závěru práce jsou navržena možná opatření, která mají vést ke zlepšení finanční situace podniku.

This bachelor’s thesis deals with an evaluation of the financial situation of the selected company between 2012 and 2016. The first part of the thesis approaches the issue of financial analysis by theoretical knowledge. The second part of the thesis includes the introduction of the company and the practical application of financial indicators. The conclusion of the thesis contains measures to improve the financial situation of the company.
Evaluation of the Financial Situation of the Selected Private Corporation and Proposals to its Improvement
Keywords: finanční analýza; PESTLE analýza; SWOT analýza; rozvaha; poměrové ukazatele; financial analyst; PESTLE analysis; SWOT analysis; balance sheet; ratio indicators